Hepatitis B Virus DNA is a substrate for the cGAS/STING pathway but is not sensed in infected hepatocytes - Lauterbach-Rivière, Lise; Bergez, Maïwenn; Mönch, Saskia; Qu, Bingqian; Riess, Maximilian; Vondran, Florian W. R.; Liese, Juliane; Hornung, Veit; Urban, Stephan; König, Renate (Viruses, 2020)
Hepatitis B virus (HBV) chronic infection is a critical risk factor for hepatocellular carcinoma. The innate immune response to HBV infection is a matter of debate. In particular, viral escape mechanisms are poorly understood. Our study reveals that HBV RNAs are not immunostimulatory in immunocompetent myeloid cells. In contrast, HBV DNA from viral particles and DNA replication intermediates are immunostimulatory and sensed by cyclic GMP-AMP Synthase (cGAS) and Stimulator of Interferon Genes (STING). We show that primary human hepatocytes express DNA sensors to reduced levels compared to myeloid cells. Nevertheless, hepatocytes can respond to HBV relaxed-circular DNA (rcDNA), when transfected in sufficient amounts, but not to HBV infection. Finally, our data suggest that HBV infection does not actively inhibit the DNA-sensing pathway. In conclusion, in infected hepatocytes, HBV passively evades recognition by cellular sensors of nucleic acids by (i) producing non-immunostimulatory RNAs, (ii) avoiding sensing of its DNAs by cGAS/STING without active inhibition of the pathway.
Gesehen am 03.09.2020